PENGARUH TINGKAT PAJAK EFEKTIF PERUSAHAAN TERHADAP PEMBERHENTIAN DIREKTUR UTAMA - Arifah Fibri Andriani; Sinabutar, Goradok Pande Raja (Scientax, 2020)
This study aims to determine the effect of the company’s effective tax rate on forced president director turnover. Prior studies find that the company’s effective tax rate is used continuously by shareholders to assess the performance of top manager (president director), then used as the basis of making decisions whether to hire or to fire the top manager. The effective tax rate of company is measured using accountancy effective tax rate (ETR) and cash effective tax rate (Cash ETR). By using 90 companies listed on the Indonesia Stock Exchange (IDX) as the samples, selected after going through purposive sampling stages, with firm-years starting from 2012 to 2016, this study finds that the company’s effective tax rate (both ETR and Cash ETR) does not affect the forced president director turnover.